EFFECT OF TRAHEOSTOMY ON THE INPATIENT TREATMENT OF PATIENTS WITH CONTACT MEDIASTINITES - Alexander L. Gromov; Mikhail A. Gubin; Sergei V. Ivanov; Denis S. Tishkov (Кубанский научный медицинский вестник, 2019)
The aim was to assess the impact of emergency and planned tracheostomy on the main indicators of inpatient treatment in patients with contact mediastinitis.Materials and methods. This work was performed on the basis of the Department of Maxillofacial Surgery of the Kursk Regional Clinical Hospital. In order to conduct a comparative assessment of the treatment results, the patients with contact mediastinitis (46 people, surveyed period 2008–2017) were divided into 2 subgroups: control (25 people, 7 women, 18 men), who were treated without a tracheostomy; and the main group (21 people: 9 women, 12 men), with tracheostomy performed. The etiological and microbiological characteristics of the disease, the total duration of inpatient treatment, the length of stay in the resuscitation and intensive care units (bed-days), the dependence of the disease outcome (death, recovery) on the form of surgical intervention (tracheostomy) were evaluated.Results. A statistically significant effect of tracheostomy on the total duration of hospitalization and mortality rate was established (p0.05). Consequently, at present this issue cannot be resolved unambiguously and requires further research and mathematical analysis.Conclusion. The implementation of tracheostomy significantly increases the duration of inpatient treatment of patients with contact odontogenic mediastinites (p0.05).Conflict of interest: the authors declare no conflict of interest.